2019
DOI: 10.1002/brb3.1310
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' attitudes toward lumbar puncture—And how to change

Abstract: Objective To survey medical students on the lumbar puncture (LP) procedure in terms of their existing knowledge, practical experience and attitudes, and to determine whether the completion of a single standardized seminar that includes practical training on phantoms can alter these parameters. Methods The survey was completed by medical students undertaking the curricular neurology course. Students were asked to describe their practical experience in different bedside p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…LP is an essential tool in daily clinical practice and despite being a relatively safe procedure performed at the patient bedside, a negative attitude appears to persist both in general population and in medical students [ 4 , 28 ]. In several studies, medical trainees associated LP with a high level of difficulty and a low level of confidence compared to other similar bedside procedures [ 29 , 30 ]. The development of simulation-based training has allowed practice in a safe environment and significantly increased confidence and real life procedural skills [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…LP is an essential tool in daily clinical practice and despite being a relatively safe procedure performed at the patient bedside, a negative attitude appears to persist both in general population and in medical students [ 4 , 28 ]. In several studies, medical trainees associated LP with a high level of difficulty and a low level of confidence compared to other similar bedside procedures [ 29 , 30 ]. The development of simulation-based training has allowed practice in a safe environment and significantly increased confidence and real life procedural skills [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cranach et al have demonstrated that LP was associated with the lowest baseline levels of experience and confidence compared to other procedures. This lack of proper teaching leads to heterogeneous practices associated with a variable rate of side effects [ 1 , 3 , 14 ]. In this study, we have demonstrated that teaching with simulation-based sessions is a good opportunity to improve the theoretical knowledge and the technical skills of LP procedure and consequently to optimize LP practice at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first four days of the clerkship, the students completed an online Likert-style survey assessing their level of confidence and perceived skill with these activities (Supplementary File 1.pdf). The design of this survey was based on previously published instruments (Dehmer et al, 2013;von Cranach, Backhaus and Brich, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…According to a 2016 survey, 57% of US medical school graduates do not perform a lumbar puncture-a crucial diagnostic procedure for neurological conditions-prior to graduation (Barr and Graffeo, 2016). Likewise, a 2019 survey of German medical students found that, out of 14 common medical procedures, the students endorsed the least confidence with performing a lumbar puncture (von Cranach, Backhaus and Brich, 2019). The Association of American Medical Colleges (AAMC) recognizes the importance of procedural skill in medical education, as reflected in its list of Entrustable Professional Activities (EPAs) that students should be able to perform upon starting residency (AAMC, 2014).…”
Section: Introductionmentioning
confidence: 99%